Research on the impact of green finance on China’s ocean economic growth under the “dual carbon” goal - Li, Yan; Huang, Yi (Frontiers in Marine Science, 2025)
IntroductionWith the introduction of the strategy of a strong marine power and the “dual-carbon” goal, green, low-carbon and sustainable development has become an important requirement for the growth of the Ocean Economy. Green finance is a financial activity that promotes environmental improvement, climate change response and efficient resource utilization. The “dual-carbon” goal is a major national strategy proposed by the Chinese Government in 2020 to achieve carbon peaking and carbon neutrality, which is a two-stage carbon emission reduction strategic goal proposed by the Chinese Government. China is committed to achieving carbon peaking by 2030, i.e., no further growth in carbon dioxide emissions after peaking, and carbon neutrality by 2060, i.e., offsetting its own carbon dioxide emissions through afforestation, energy conservation and emission reduction. This goal is not only an important initiative for China to address climate change, but also has a profound impact on global climate governance. Through the support of green finance, China is promoting the green transformation and sustainable development of its ocean economy while realizing the “dual carbon” goal. As one of the world’s largest ocean economies, with more than 18,000 kilometers of coastline and an ocean GDP that accounts for 7.8% of the country’s GDP, the development of the ocean economy has a significant impact on the sustainable use of global ocean resources. Therefore, it is of great practical significance for this paper to explore the impact of green finance on China’s ocean economy growth under the “dual-carbon” goal based on the data of China’s coastal provinces and cities from 2008 to 2022.MethodsThis paper constructs green finance index comprehensive evaluation system, calculates green finance index of Chinese coastal provinces and cities, This paper uses a fixed-effects model to analyze the role of green finance in achieving the ‘dual-carbon’ goal and fostering the growth of China’s ocean economy, and combines with the threshold effect model to further study the nonlinear role of green finance on China’s ocean economy. The paper takes green finance as the core explanatory variable. In this paper, green finance is taken as the core explanatory variable, per capita gross domestic product (GDP) as the explanatory variable, income from marine scientific research and the scale of marine industry as the threshold variables, and the number of authorized patents, GDP index, stock market activity, energy consumption structure, the scale of the tertiary industry and the scale of the secondary industry as the other control variables.ResultsIt is found that 1) Green finance has a positive effect on China’s ocean economic growth, with the strongest positive effect on the Southern Ocean Economic Zone. 2) The scale of the marine industry, the scale of the tertiary industry, and the scale of the secondary industry have a significant positive effect on the ocean economic growth in the Nouthern, Eastern, and Southern Ocean Economic Zones, as well as in China as a whole. In addition, the stock market activity has a positive contribution from a national perspective, but a negative hindering effect in the Northern Ocean Economic Zone. 3) The gross regional product index, stock market activity, and energy consumption structure in the Northern Ocean Economic Zone have a negative hindering effect, and the gross regional product index has the most negative hindering effect. The negative hindering effect of the number of authorized patents, GDP index and stock market activity is not significant in the Eastern Ocean Economic Zone, and the negative hindering effect of the income of marine scientific research institutions, GDP index and stock market activity is not significant in the Southern Ocean Economic Zone. From a national perspective, the number of authorized patents has a negative hindering effect, but it has a significant positive promoting effect in the Southern Ocean Economic Zone. 4) The intensity of the positive promoting effect of green finance on China’s ocean economic growth is non-linear, and when the index of the income from the funding of marine-based scientific research institutes reaches 11.249, the promoting effect of green finance on the growth of the ocean economy is slightly weakened. When the marine industry scale index reaches -1.9661, the promotion effect of green finance on ocean economic growth will be significantly weakened.DiscussionThis paper comprehensively evaluates the development of green finance in China’s coastal provinces and municipalities by constructing a comprehensive evaluation system of green finance indexes suitable for the ocean economic field, dividing the study area into the Northern Ocean Economic Zone, the Eastern Ocean Economic Zone and the Southern Ocean Economic Zone, and investigating the role of green finance on China’s ocean economic growth under the goal of “dual-carbon” and its spatial variability. The study will examine the role of green finance on China’s ocean economic growth under the “dual-carbon” goal and the spatial variability, and combine with the threshold effect model to further clarify the nonlinear relationship of green finance on China’s Ocean Economy, so as to provide valuable countermeasure suggestions for policy makers.